Pleural and pericardial effusion associated with infection in a feline patient - Ana Torrano Guillamón; Casandra Juarez Sarrión; Alejandra Álvarez Fernández; Laia Solano-Gallego; Carlos González Villajos; Carolina Arenas Bermejo; Jorge Castro López (Journal of Feline Medicine and Surgery Open Reports)
Case summary A 7-year-old female spayed domestic shorthair cat was presented to our hospital with a 2-day history of anorexia, dyspnoea and lethargy. Blood tests revealed mild anaemia (packed cell volume [PCV] 22.4%) and the biochemistry panel was unremarkable. Thoracic radiographs and echocardiography showed the presence of pericardial effusion with cardiac tamponade as well as pleural effusion. During the initial attempt at pericardiocentesis, a small sample was obtained, sufficient only for fluid analysis and cytology. Subsequently, the pericardial effusion immediately resolved, presumably owing to the drainage of pericardial fluid into the pleural space. Thoracocentesis was then performed, yielding 50 ml of fluid. The analysis of the fluid was consistent with a protein-rich transudate associated with macrophagic-neutrophilic inflammation in both sampled areas. PCR was positive for Bartonella henselae in the pleural/pericardial fluid pool and peripheral blood. Bacterial culture was negative and feline coronavirus real-time PCR was negative. The patient was treated with marbofloxacin 5 mg/kg PO q24h for 5 weeks. No clinical signs were reported at this time; however, blood B henselae PCR remained positive. Treatment was changed to doxycycline at 5 mg/kg PO q12h for 6 weeks. The cat remained subclinical throughout the treatment, and a blood PCR after 6 weeks yielded negative results. Relevance and novel information  To the best of the authors’ knowledge, the present clinical findings related to B henselae infection in a cat without concurrent heart failure have not been previously documented. This clinical case highlights the need to include Bartonella species as a differential diagnosis in cats with protein-rich transudate effusions associated with neutrophilic-macrophagic inflammation and fever.